Lung carcinoid tumours: histology and Ki‐67, the eternal rivalry. Issue 2 (26th October 2022) - Centonze, Giovanni; Maisonneuve, Patrick; Simbolo, Michele; Lagano, Vincenzo; Grillo, Federica; Fabbri, Alessandra; Prinzi, Natalie; Garzone, Giovanna; Filugelli, Martina; Pardo, Carlotta; Mietta, Alessia; Pusceddu, Sara; et al.
Abstract : WHO classification of Thoracic Tumours defines lung carcinoid tumours (LCTs) as well‐differentiated neuroendocrine neoplasms (NENs) classified in low grade typical (TC) and intermediate grade atypical carcinoids (AC). Limited data exist concerning protein expression and morphologic factors able to predict disease aggressiveness. Though Ki‐67 has proved to be a powerful diagnostic and prognostic factor for Gastro‐entero‐pancreatic NENs, its role in lung NENs is still debated. A retrospective series of 370 LCT from two oncology centers was centrally reviewed. Morphology and immunohistochemical markers (Ki‐67, TTF‐1, CD44, OTP, SSTR‐2A, Ascl1, and p53) were studied and correlated with Overall Survival (OS), Cancer‐specific survival (CSS) and Disease‐free survival (DFS). Carcinoid histology was confirmed in 355 patients: 297 (83.7%) TC and 58 (16.3%) AC. Ki‐67 at 3% was the best value in predicting DFS. Ki‐67 ≥ 3% tumours were significantly associated with AC histology, stage III‐IV, smoking, vascular invasion, tumour spread through air spaces OTP negativity, and TTF‐1, Ascl1 and p53 positivity. After adjustment for center and period of diagnosis, both Ki‐67 (≥3 versus <3) and histology (AC versus TC) alone significantly added prognostic information to OS and CSS multivariable model with age, stage and OTP; addition of both variables did not provide further prognostic information. Conversely, an improved significance of the DFS prediction model at multivariate analysis was seen by adding Ki‐67 (≥3 versus <3, P adj = 0.01) to TC and AC histological distinction, age, lymph node involvement, residual tumour and OTP. Ki‐67 ≥ 3% plays a potentially pivotal role in LCT prognosis, irrespective of histological grade. Abstract : Lung Carcinoid Tumours: Histology or Ki‐67 Index?